Peculiar Minerogenetic Cave Environments of Mexico: The Cuatro Ciénegas Area - Forti, Paolo; Galli, Ermanno; Rossi, Antonio (Acta Carsologica, 2006)
The karst area of Quatro Ciénegas (Coahuila, Mexico) represents an ideal site to study cave mineralogy, because it hosts caves of different age and genesis (karst, thermal, mine caves). Among the speleothems studied is worth to mention a nest of aragonite cave pearls found deep inside the Reforma mine characterized by the total absence of growing layers inside them. Despite only few studied caves (8), some 32 different cave minerals have been detected, one of which is new for the cavern environment (kingsmountite) and another one, still under study, which probably will result new for science. Due to the scientific interest of their chemical deposits it should be very important to protect in the future the natural cavities of the karst systems of Cuatro Ciénegas in order to preserve a scientific patrimony, actually only partially known.